Palynotaxonomy of the cretaceos to neogene section of the pelotas brasin, brasil: Dinoflagellate cysts of ptychodiscales and gonyaulacales orders - Premaor, Eduardo; Souza, Paulo A.; Ferreira, Elizabete P.; Guerstein, G. Raquel; Arai, Mitsuru [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
Dinoflagellate cysts are commonly used to obtain the relative ages, correlations and paleoenvironmental interpretations of the Cretaceous and Paleogenic sections of the Brazilian continental margin. However, the micropaleontological data of the Pelotas Basin is mainly concerning to calcareous microfossils, which is not true for the sedimentary deposits of the Pelotas Basin, whose micropaleontological informations is mostly referring by calcareous microfossils. In this second contribution, we present the systematic and descriptive detailing of the dinoflagellates cysts of the Ptychodiscales and Gonyaulacales orders, from the analysis of 535 samples collected from two wells (BP-01 and BP-02) drilled by Petrobras S.A. in the offshore portion of the Pelotas Basin. The levels analyzed are rich and diverse, enabling the recognition of 137 species. In greater numbers, cysts belonging to the Order Gonyaulacales include 76 genera, 133 species, besides three sub-species. Two genera and four species were assigned to the Order Ptychodiscales. Among the described taxa, 72 are cited for the first time for the Brazilian basins. The recognized associations indicated ages between the Cretaceous and the Neogene, based on the occurrences of E. dettmanniae, D. acuminatum and O. indigena for the Cretaceous; D. californica, D. carposphaeropsis and E. reticulata for the Paleocene; B. longissimum, M. fimbriatum and M. perforatum for the Eocene; C. galea, C. aubryae and H. obscura for the Miocene. R. actinocoronata and A. andalousiensis recorded at the post-Miocene levels of the basin are indicative of younger ages, possibly positioned between the Pliocene and the Pleistocene.
Palinotaxonomia da seção cretácea a neogena da bacia de pelotas, brasil: Cistos de dinoflagelados das ordens ptychodiscales e gonyaulacales
Keywords: Gonyaulacaleans cysts; Gymnodinian cysts; Neogene; Palynology; Taxonomy; Upper cretaceous